Os recursos léxico-gramaticais de atitude no discurso de dois professores universitários - Almeida, Fabíola Ap. Sartin Dutra Parreira (2008)
This research is one of the many that belong to a project called DIRECT from the LAEL- PUC-SP Program. Its main objective is to investigate the lexicogrammar resources of the Attitude subsystem in classroom speeches of two university teachers. The participants were chosen after an informal interview with the students of the Law and Language courses where they were asked about who they considered the best teachers. Their preference was compared to the result of an institutional evaluation, which confirmed their choice. The context of this research is a university located in the west-central region of Brazil. Investigating the attitude subsystem, which belongs to the Appraisal system, realized in the spoken discourse of two teachers, this study aims to bring contributions to applied linguistic researches, especially from the point of discourse analyses based on the systemic functional grammar. Therefore, it uses the Halliday (1978,1985/1994); Martin (1992); Eggins (1994); Thompson (1996); Eggins and Slade, (1997); Halliday and Matthiessen (2004) studies. In addition, more specifically on the studies about Appraisal - Martin (2000); Martin e Rose (2003/2007); Martin e White (2005); White (2004). The data were taken from classroom and interview recordings of the two teachers. The Eggins and Slade (1997) suggestions for methodological procedures was adopted for the data analyses such as the identification of the lexical grammar elements which realized the attitude in discourse, the classification of those elements by the attitude type and their interpretation under the attitude concepts. The data showed that the attitude which was realized by the attributes, epithets and processes in the teacher s discourse were used in order to get a solidarity response from the students about the teacher s theoretical and methodological behavior in the classroom. This research reviewed that the attitude analysis can be helpful for the understanding of interpersonal meanings, so when expressing opinions and evaluations about emotions, people s behavior and about things, objects and processes, the speaker/reader intends to get a solidarity response from the listener/reader. The comprehension of such attitudes contributes for the communication between the members of a community